Fraud and Corruption in Football: Lessons from a Survey of Match-Fixing in Cyprus - Krambia-Kapardis, Maria; Levi, Michael (My University, 2023)
Purpose The purpose of this paper is to identify if fraud theory models suggested over the years are applicable to match-fixing and if so, whether the Krambia-Kapardis’ (2016) holistic fraud and corruption prevention model can be used to reduce significantly match-fixing in football. Design/methodology/approach An online survey was developed by the authors and was administered to football stakeholders in Cyprus, namely, players, referees, coaches and team management. Findings The research questions, who are the initiators of match-fixing, why is match-fixing taking place and what is the best way to prevent or reduce match-fixing, have been answered, and these findings have enabled the authors to make policy recommendations. Research limitations/implications The survey considered match-fixing in only one sport (football) while the number of respondent categories and the 335 usable questionnaires returned did not allow advanced statistical analysis of the data obtained. Practical implications The findings point to the need both for ethics and moral values to be installed in all the stakeholders through training and continuing education. It is also suggested that teams/clubs and related associations acting as regulators ought to implement governance principles and ethical programs, including whistleblowing lines and appoint integrity officers to minimize the match-fixing phenomenon. Furthermore, society, as well as government, sport regulators and sponsors, ought to encourage and demand fair play and integrity in sport through improved measures of governance and accountability and the implementation of ethical audits and public disclosure of audited financial statements of teams. Finally, sports integrity ought to be embedded in school curriculum from a very young age. Originality/value To the best of the authors’ knowledge, this is an original contribution to knowledge that has impact on the future of sporting fairness and social legitimacy.
Keywords: Match fixing; Gambling; Football Corruption; Whistleblowing; Football; Fraud; Corruption; Prevention